2000
DOI: 10.1007/s004110000062
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of the vertical migration of fallout 137 Cs in the soil of a pasture, and consequences for long-term predictions

Abstract: Various transport models are presently used to predict the long-term migration behaviour of fallout radiocesium on the soil. To examine to what extent the uncertainty of these predictions is influenced by the spatial variability of the migration rates, we determined the depth profiles of Chernobyl-derived 137Cs at 100 plots in a 100 m x 100 m pasture. These data were used to obtain the frequency distributions of the characteristic transport parameters of three widely used transport models (e.g. dispersion-conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Bossew and Strebl (2001), Schuller et al (1997) and Szerbin et al (1999), representing such different ecosystems like tropical rainforest, permanent pastures in Chile and Hungarian grassland soils. At an alpine pasture, Bunzl et al (2000) found also very small migration rates of 137 Cs. Evaluating more than 500 vertical distributions of radionuclides (not only radiocesium) in Austria, Bossew and Kirchner (2004) state that typical orders of magnitude of the velocities and the diffusion constants of Chernobyl-134 Cs are 0.3 cm a ÿ1 and 0.3 cm 2 a ÿ1 , respectively.…”
Section: Evaluation Of the Depth Distributions By The Convection-dispmentioning
confidence: 94%
“…Bossew and Strebl (2001), Schuller et al (1997) and Szerbin et al (1999), representing such different ecosystems like tropical rainforest, permanent pastures in Chile and Hungarian grassland soils. At an alpine pasture, Bunzl et al (2000) found also very small migration rates of 137 Cs. Evaluating more than 500 vertical distributions of radionuclides (not only radiocesium) in Austria, Bossew and Kirchner (2004) state that typical orders of magnitude of the velocities and the diffusion constants of Chernobyl-134 Cs are 0.3 cm a ÿ1 and 0.3 cm 2 a ÿ1 , respectively.…”
Section: Evaluation Of the Depth Distributions By The Convection-dispmentioning
confidence: 94%
“…Sutherland (1996) summarized the most complete literature review on reference sites. Bunzl et al (1997Bunzl et al ( , 2000, Schuller et al (1997), Lettner et al (2000), and Golosov et al (1999) provide more-recent information on selection of and variability within reference sites, while Pennock (2000) placed variability in reference sites in the context of variability in other soil properties.…”
Section: Selection Of Reference Sitesmentioning
confidence: 98%
“…This would make long-term dose estimates for other radionuclides somewhat conservative, if based on the same migration data. The vertical migration of contaminants in soil is described in ERMIN by a one-dimensional, convectiveedispersive, local equilibrium, mass transport model, as suggested by Bunzl et al (2000). This gives the contaminant concentration as a function of depth and time, thus facilitating multiplication at different times of contamination level values at different depths by appropriate dose rate conversion factors.…”
Section: The Euranos Dose Model For Inhabited Areasmentioning
confidence: 99%